2021
DOI: 10.3389/fmicb.2021.760698
|View full text |Cite
|
Sign up to set email alerts
|

Finafloxacin, a Novel Fluoroquinolone, Reduces the Clinical Signs of Infection and Pathology in a Mouse Model of Q Fever

Abstract: Finafloxacin is a novel fluoroquinolone with optimal antibacterial activity in low pH environments, therefore offering a therapeutic advantage over some traditional antibiotics, in treating bacterial infections associated with acidic foci. Coxiella burnetii, the causative agent of Q fever, is a bacterium which resides and replicates in acidic intracellular parasitic vacuoles. The efficacy of finafloxacin was evaluated in vivo using the A/J mouse model of inhalational Q fever and was compared to doxycycline, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…Previous work performed at Dstl has demonstrated broad spectrum in vitro activity of finafloxacin against Francisella tularensis, Yersinia pestis, Coxiella burnetii, Bacillus anthracis, Burkholderia pseudomallei , and Burkholderia mallei ( Barnes et al, 2019a ; Peyrusson et al, 2021 ). In vivo efficacy has also been demonstrated against F. tularensis, Y. pestis, C. burnetii , and B. pseudomallei ( Barnes et al, 2017 , 2019b , 2021 ; Hartley et al, 2021 ). It has been suggested that this is due to the rapid influx of finafloxacin into cells, the accumulation to high levels within the cell, and a slow efflux rate ( Chalhoub et al, 2019 ).…”
Section: Introductionmentioning
confidence: 98%
“…Previous work performed at Dstl has demonstrated broad spectrum in vitro activity of finafloxacin against Francisella tularensis, Yersinia pestis, Coxiella burnetii, Bacillus anthracis, Burkholderia pseudomallei , and Burkholderia mallei ( Barnes et al, 2019a ; Peyrusson et al, 2021 ). In vivo efficacy has also been demonstrated against F. tularensis, Y. pestis, C. burnetii , and B. pseudomallei ( Barnes et al, 2017 , 2019b , 2021 ; Hartley et al, 2021 ). It has been suggested that this is due to the rapid influx of finafloxacin into cells, the accumulation to high levels within the cell, and a slow efflux rate ( Chalhoub et al, 2019 ).…”
Section: Introductionmentioning
confidence: 98%
“…Therefore, it could be hypothesized that the reduced rate of clearance might impact the development of long-term conditions. Along with slower clearance, we have some evidence of bacteria being trafficked systemically during treatment both in this study with doxycycline and previously with Finafloxacin, another bacteriostatic antibiotic [43]. Despite extending the infection model out to more than 35 days, complete clearance of the infection was not seen in any of the treated groups.…”
Section: Discussionmentioning
confidence: 60%
“…Finafloxacin has been evaluated in preclinical and clinical studies that have shown that finafloxacin has increased bactericidal activity at infection-relevant acidic pH against intracellular Legionella pneumophila , ciprofloxacin resistant strains of Escherichia coli and Acinetobacter baumannii , and other Gram-negative and Gram-positive bacterial species ( Emrich et al, 2010 ; Higgins et al, 2010 ; Dalhoff et al, 2011 ; Lemaire et al, 2011 ; Stubbings et al, 2011 ; Vente, 2015 ). Furthermore, we have previously demonstrated that finafloxacin has in vitro activity and in vivo efficacy against a range of biothreat pathogens including Yersinia pestis, B. pseudomallei, Francisella tularensis, Bacillus anthracis , and Coxiella burnetii ( Barnes et al, 2017 , 2019 , 2021 ; Hartley et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%